FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERBILLIRUBINEMIA PADA BAYI BARU LAHIR DI RSUD RADEN MATTAHER JAMBI TAHUN 2017-2018 - Dewi Riastawaty (Jurnal Maternitas Kebidanan, 2019)
Hiperbillirubin in the newborn occur in 25-50% neonatal enough months and higher in preterm neonates. Data obtained from Provincial Hospital Raden Mattaher Jambi by the year 2016 as many as 20 cases, the year 2017 as many as 15 cases and in 2018 as much as 29 cases. This research aims to know the factors associated with the incidence of hiperbillirubinemia in the Provincial Hospital of Raden Mattaher Jambi years 2017-2018.This research is the research design of case control analytic. This research was conducted at the Provincial Hospital of RadenMattaher Jambi in June-July 2019. The population of the research was divided into two populations is newborn cases with hiperbillirubinemia years of 2017-2018 as much as 44 babies and population control is a normal newborn baby in 2017-2018 as many as 973 baby. The sample in this research is divided into two samples as many as 44 cases babies were taken with the technique of total sampling and sample controls as much as 44 babies taken with 1:1 ratio with simple random sampling technique. Data obtained using sheet checklist. Data analysis in this research areUnivariate and bivariat. There is a connection between hypoglycemia (p = 0,032) and Low Birth Weight (p = 0.006) and with hiperbillirubinemia in the newborn with a p value < 0.05. There is no relation between incidence of hypoglycemia with hiperbillirubinemia in the newborn with a p value of 0.668 > 0.05.The expected results of this research can improve health services to medical personnel and mothers maternity covering the State of mother and encourage mothers to do checks sugar levels, as well as minimizing the use of oxytocin on time delivery as well as nutritional intake is insufficient to suggest while pregnant.